A Synthetic Small RNA Homologous to the D-Loop Transcript of mtDNA Enhances Mitochondrial Bioenergetics - Mathuram, Theodore L.; Townsend, Danyelle M.; Lynch, Vincent J.; Bederman, Ilya; Ye, Zhi-Wei; Zhang, Jie; Sigurdson, Wade J.; Prendergast, Erin; Jobava, Raul; Ferruzza, Jonathan P.; D’Angelo, Mary R.; Hatzoglou, Maria; et al. (Frontiers in Physiology, 2022)
Mitochondrial malfunction is a hallmark of many diseases, including neurodegenerative disorders, cardiovascular and lung diseases, and cancers. We previously found that alveolar progenitor cells, which are more resistant to cigarette smoke-induced injury than other cells of the lung parenchyma, upregulate the mtDNA-encoded small noncoding RNA mito-ncR-805 after exposure to smoke. mito-ncR-805 acts as a retrograde signal between mitochondria and the nucleus. Here, we identified a region of mito-ncR-805 that is conserved in mammalian mitochondrial genomes and generated shorter versions of mouse and human transcripts (mmu-CR805 and hsa-LDL1, respectively), which differ in a few nucleotides and which we refer to as the “functional bit.” Overexpression of mouse and human functional bits in either mouse or human lung epithelial cells led to increased Krebs cycle activity and oxidative phosphorylation, stabilized the mitochondrial potential, conferred faster cell division, and lowered levels of pro-apoptotic pseudokinase TRIB3. Both oligos conferred cross-species beneficial effects. Our data indicate a high degree of evolutionary conservation of retrograde signaling via a functional bit of the D-loop transcript, mito-ncR-805, in mammals. This emphasizes the importance of the pathway and suggests the potential to develop this functional bit into a therapeutic agent that enhances mitochondrial bioenergetics.